Assessing the Impact of Standby Charges on the Financial Viability of Rooftop Solar PV Systems in Malaysia - Shuhaimi Ismail; Kusaini, Khazaren; Siran, Shahrulnizam; Abdullah, Kamil (International Journal of Integrated Engineering, 2026)
This study investigates the economic impact of standby charges on a 6.9 MWp commercial rooftop solar photovoltaic (PV) system operating under Malaysia’s Self-Consumption (SELCO) regulatory framework. Using actual performance data and a 21-year project horizon, a parametric analysis was performed to evaluate the sensitivity of four key economic indicators; simple payback period, internal rate of return, net present value, and levelized cost of energy to standby charges levels ranging from RM 0.00 to RM 12.00 per kWp per month. Results show that increasing standby charges significantly reduces project feasibility. The SPP extended from 9.84 to 28.07 years, IRR declined from 7.98 % to negative (2.10 %), and NPV shifted from RM 4.47million to negative (RM 8.27million), with the break-even point occurring near RM 4.00 and RM 5.00/kW/month. Similarly, LCOE increased from RM 0.192 to RM 0.334/kWh, exceeding the grid tariff of RM 0.27/kWh at around RM 6.00/kW/month. These trends indicate that standby charges above RM 4.00/kW/month compromise investment viability. The findings highlight the need for balanced regulatory design to ensure grid reliability while sustaining investor confidence. The developed analytical framework and heat-map representation provide a practical reference for policymakers to optimize standby-charge levels and promote sustainable rooftop solar PV deployment in Malaysia.